APLIKASI FILTER KERAMIK BERBASIS TANAH LIAT ALAM DAN ZEOLIT PADA PENGOLAHAN AIR LIMBAH HASIL PROSES LAUNDRY - Subriyer Nasir (Bumi Lestari Journal of Environment, 2013)
AbstractCeramic filters made of natural clay and zeolite were used to treat the efluent from laundryindustry in Palembang. The pretreatment process using silica and active carbon was appliedto the samples prior feed to the ceramic filter. Process variables studied were operatingtime and the filters composition. Parameters analyzed were TDS (Total Dissolved Solid),pH, EC (Electrical Conductivity), COD (Chemical Oxygen Demand), BOD (BiologicalOxygen Demand) and the concentration of LAS (Linear Alkylbenzene Sulphonate). Theresults showed that ceramic filters combined with silica and activated carbon can reducethe LAS concentration in detergent wastewater up-to 97%. Scanning Electron Microscope(SEM) images shows that filter could be categorized as microfiltration filter with randomporous structures.